2018
DOI: 10.3390/molecules23051160
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin 3-Gallate Synthetic Analogues Inhibit Fatty Acid Synthase and Show Anticancer Activity in Triple Negative Breast Cancer

Abstract: (−)-Epigallocatechin 3-gallate (EGCG) is a natural polyphenol from green tea with reported anticancer activity and capacity to inhibit the lipogenic enzyme fatty acid synthase (FASN), which is overexpressed in several human carcinomas. To improve the pharmacological profile of EGCG, we previously developed a family of EGCG derivatives and the lead compounds G28, G37 and G56 were characterized in HER2-positive breast cancer cells overexpressing FASN. Here, diesters G28, G37 and G56 and two G28 derivatives, mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…Particularly, the monoesters inhibited the growth of MDA-MB-231 cells more than the diesters, and only the monoesters induced the apoptosis detected by poly (ADP-ribose) polymerase (PARP) cleavage. Altogether, these results suggest that these polyphenolic compounds, particularly the monoesters, due to their inhibitory role on FASN, could represent a new strategy for TNBC treatment [26].…”
Section: An Overview Of the Role Of Egcg In Tnbc Cells Growth: Findinmentioning
confidence: 79%
“…Particularly, the monoesters inhibited the growth of MDA-MB-231 cells more than the diesters, and only the monoesters induced the apoptosis detected by poly (ADP-ribose) polymerase (PARP) cleavage. Altogether, these results suggest that these polyphenolic compounds, particularly the monoesters, due to their inhibitory role on FASN, could represent a new strategy for TNBC treatment [26].…”
Section: An Overview Of the Role Of Egcg In Tnbc Cells Growth: Findinmentioning
confidence: 79%
“…Both compounds have the ability to internalize and inhibit FASN activity as observed in parental PC9 cells (Figure 4), however G28 was of average 5.5 times more effective than EGCG. We have previously shown the ability of the natural compound EGCG to inhibit FASN activity in wild type EGFR NSCLC cells and different breast cancer subtypes [40,43]. Despite their cytotoxicity, only the synthetic compound significantly reduced FASN activity in GR models (Figure 4).…”
Section: Discussionmentioning
confidence: 90%
“…To date, many EGCG derivatives have been developed to improve efficacy and increase stability in physiological conditions. Among them, the naphthalene derivative G28 has shown interesting antiproliferative features against sensitive and resistant breast cancer cells [38,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, EGCG displays low potency, poor bioavailability, and limited stability. Crous-Maso et al (95) reported on the design and synthesis of a novel collection of polyphenolic compounds, containing two galloyl moieties (3,4,5-trihydroxybenzoyl group) linked by a variable cyclic subunit. These molecules were tested alongside EGCG for their anticancer properties, in particular in TNBC cell models.…”
Section: Egcgmentioning
confidence: 99%